HARMONIC INVESTIGATION IN LOW AND MEDIUM VOLTAGE NETWORKS USING COMPUTER SIMULATION AND MEASUREMENT DEVICES - Egner, Sean Robert William (My University, 2006)
This dissertation discusses the development of an ATP model of a network to aid measurement techniques in a harmonic evaluation. A theoretical back- ground discussion of various pieces of equipment and their signicance to har- monics is included. National Electricity Regulator (NRS 048) standards are discussed with refer- ence to performing a basic investigation and short comings. A test study was performed on the Brandspruit Mine in Secunda. ATP models are developed for equipment relevant to the test case, these in- clude AC{AC converters, AC{DC converters, three phase transformers and cables. Finally the measured test case is compared to simulation results and conclusions drawn.
Student Number : 9811492X - MSc dissertation - School of Electrical and Information Engineering - Faculty of Engineering and the Built Environment
Keywords: harmonics; ATP; modelling; variable speed drives; VSO